MIP-VR: An omnidirectional navigation and jumping method using IMU in VR HMD - Juyoung Lee; Gerard Jounghyun Kim; Ahn, Sang Chul; Jae-In Hwang (IEEE, 2019)
We suggest an omnidirectional navigation and jumping method using walking-in-place (WIP) interface. This method supports forward, backward, sideways walking and jumping include vertical jump. The shooting game is one of the contents that can best take advantage of VR. Since the WIP interface is a hands-free navigation method, it works well with VR shooting game. However, we need to extend WIP because this interface is not possible for sideways walking and jumping that is possible with existing keyboards or joysticks. We propose a forward and sideways walking method suitable for VR shooting game. Our method is inspired by human behavior and using a state diagram to support backward walking, running and vertical jump. We call it motion-in-place (MIP). Our method uses inertial measurement unit (IMU) only. A pilot test of 10 subjects showed that our method is less tiring and useful than a forward-only WIP interface. Our method can be used for most HMDs with built-in IMU and can be suitable for VR shooting game.
Keywords: virtual reality; navigation; walk in place